Economic Struggles, Resilience and Agency: Ageing Market Women Redefining 'Old' in Kampala, Uganda - Ruth Nsibirano; Consolata Kabonesa; Evelyne Lutwama-Rukundo; Euzobia M. Mugisha Baine (Gender a Výzkum)
This article documents evidence from a qualitative study in which 67 in-depth interviews and a focus group discussion were conducted with aging and old market women. The study focused on what 'old' means, how aging and old market women redefine the meaning of 'old' to gain economic independence. The findings indicate that the meaning is still greatly attached to physical changes; there are differences in how different individuals respond to the changes, some challenge the gender stereotypes and prejudice attached to old age and show resilience. Indicators of resilience among market women included: an active economic lifestyle, asset ownership, the freedom to socialize and ability to make decisions about what it is they value, and ability to earn an income. Indeed, aging women in market trade have reduced dependence. To these women, seniority in age was no longer a challenge, nor a source of distress; rather, a motivator for pushing forward. Based on the findings, the authors recommend extension of social security grants to enable even more old persons to start and maintain economically rewarding ventures.